The LOX1 Gene Polymorphisms and Coronary Artery Disease in North Indian Population - Kaur, Naindeep; Singh, Jagtar; Reddy, Sreenivas (Archives of Clinical and Biomedical Research, 2019)
Background: The lectin-like oxidized-LDL receptor 1 (LOX1) is considered as a key receptor for internalizing oxidized LDL (oxLDL) and hence influencing manifestation of coronary artery disease (CAD). Aim: The study aimed to explore the association of LOX1 rs11053646 G/C and rs1050283 C/T polymorphisms and the risk of CAD in North Indian population. Methods: Angiographically confirmed 500 CAD patients and 500 healthy controls were recruited and genotyped by PCRRFLP. Results: Multiple logistic regression revealed mutant genotype of both the polymorphisms viz. CC of rs11053646 and TT of rs1050283 to confer CAD risk after adjustment for confounders (p<0.001, OR=3.072, 95% CI (1.765-5.347) and p<0.001, OR=3.487, 95% CI (1.945-6.254) respectively). Risk association was reported in recessive model for both the polymorphisms indicating that two copies of the allele are required for disease manifestation. Stratified analysis on the basis of gender showed risk association in males for both the polymorphisms with the mutant genotype exhibiting highly significant p values. However, only the LOX1 rs11053646 G/C showed the risk association in females in the mutant genotype with OR=3.179, 95% CI (1.071-9.438) and p=0.037. Stratified analysis for age reported that the mutant genotypes for both the polymorphisms significantly contributed to CAD risk in subjects above 40 years of age with OR=3.702, 95% CI (1.962-6.983) and a highly significant p<0.001 for rs11053646 G/C and OR=4.308, 95% CI (2.198-8.445) and p<0.001 for rs1050283 C/T. Conclusion: The study reveals that LOX1 rs11053646 G/C and rs1050283 C/T polymorphisms increase CAD risk in the <p style="text-align: